MORFOLOGI KAWASAN PECINAN KOTA MAGELANG - Refranisa, Refranisa (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2020)
The Chinatown area around the Liong Hok Bio Temple area is one of the areas in Magelang City which is known by many as a trade center. The morphology of the Chinatown area of Magelang City can be seen from the structure of the formation of road patterns, changes in plots, and the presence of buildings with characters that are still standing. The occurrence of these developments has the potential to change and destroy the history that is the architectural heritage of the city. This study aims to determine the morphological characteristics of the developments that occur, so that in the future it can determine the appropriate development concept for the Chinatown area of Magelang City based on Tissue Analysis. From this research, it is known that Chinatown area forms a historic urban area which has a certain character as an area that has strength in the development of the city of Magelang. This will be used as a reference in basic concept for developing the Chinatown in Magelang City as a